2021
DOI: 10.3390/min11080803
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Demolished Concretes with Three Different Strengths for Recycling as Coarse Aggregate

Abstract: This paper presents a physical characterization for the recycling into new concretes of three comminuted concretes: C16/20 (“ordinary concrete”), C50/60 (“high strength concrete”), and C70/85 (“very high strength concrete”). The top size of the crushed concretes was 19.1 mm and the size range was 4.75 to 19.1 mm. The characterization was carried out with coarse aggregate liberation, to be prepared and concentrated in a gravity concentration process. The density distribution of the coarse aggregate, cement past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…the HRA product was more concentrated with low-strength concrete, whereas the CRA product had more high-strength concrete. The liberation degree of cement paste may have played a role in this trend, as reported in the recent work by Sampaio et al [28]. In their study, concretes with lower strengths showed a better liberation of aggregates from cement paste, thus facilitating their concentration in denser fractions during density separation.…”
Section: Separation Processsupporting
confidence: 60%
“…the HRA product was more concentrated with low-strength concrete, whereas the CRA product had more high-strength concrete. The liberation degree of cement paste may have played a role in this trend, as reported in the recent work by Sampaio et al [28]. In their study, concretes with lower strengths showed a better liberation of aggregates from cement paste, thus facilitating their concentration in denser fractions during density separation.…”
Section: Separation Processsupporting
confidence: 60%
“…Recycled sand is primarily used for roads, concrete and backfill applications [10]. Characteristics of recycled aggregate are important for its reuse and they are heavily influenced by the nature of CDW waste, its processing method and the presence of impurities such as sulfate, chlorides, etc., which affect aggregate quality and limit its use for structural and high-strength concrete [11,12]. For structural concrete, French standards recommend a maximum of 30% replacement of natural aggregate.…”
Section: Introductionmentioning
confidence: 99%